Managing global offshoring strategies : a case approach - Pyndt, Jacob (Copenhagen Business School Press, 2006)
Addressing the challenges associated with managing global offshoring strategies, this book aims to "put a face" on some Danish companies as they engage in offshoring projects. It is aimed at bachelor, master and MBA students taking courses on global strategy. It is also useful in conjunction with a set of articles on global strategy issues.